Intention of Women of Reproductive Age Participation on the Visual Inspection with Acetic Acid Uptake - Nursanti, Devy Putri; Ellina, Agusta Dian (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: The biggest problem in preventing cervical cancer depends on the compliance of women of childbearing age in carrying out a Visual Inspection with Acetic Acid (Via) examination, while obedient behavior will arise if there is a strong and consistent intention. Analyzing the effect of intention as a mediating variable between attitude, subjective norm and behavioral control on the behavior of VIA examination participation in women of reproductive age. Subjects and Method: A cross-sectional study was conducted on 164 women of childbearing age who were married in the working area of ​​the Pesantren I Public Health Center, Kediri City. The independent variables (attitude, subjective norms, behavioral control), and the dependent variable (behavior), and the mediating variable (intentions). The sampling technique used simple random sampling. The questionnaire in this study was divided into two parts, the first part consisted of demographic details of the respondents and the second part related to the research variables. The analysis technique in this study uses path analysis. Results: This study shows that attitudes, subjective norms, and control behavior do not have a direct influence on behavior, but have an indirect influence with intention as a mediating variable. Conclusion: This study shows that attitudes, subjective norms, and control behavior do not have a direct influence on behavior, but have an indirect influence with intention as a mediating variable, this is in accordance with the behavioral constructs of the Theory of Planned Behavior. This means that the influence of Intention as a mediating variable between Attitude, Subjective Norm and Behavioral Control on the Behavior of VIA examination participation in women of childbearing age has been proven true. Keywords: theory of planned behavior, visual inspection of acetic acid, women of childbearing. Correspondence: Devy Putri Nursanti, Institute of Health Sciences Strada Indonesia, Jl. Manila 37, Sumberece Kota Kediri, E-mail: devyputri12@gmail.com, Phone: +62 812-5909-6664.